Tungsten - tungsten trioxide electrodes for the long-term monitoring of corrosion processes in highly alkaline media and concrete-based materials - Kolar, Mitja (Acta chimica slovenica, 2010)
The determination of pH in highly alkaline solutions and concrete materials is extremely important for monitoring or predicting the corrosion processes of reinforced concrete structures and to follow the hydration process of Portland cement, fly-ash, micro silica and other materials used in concrete manufacturing. The corrosion of reinforced concrete structures and the hydration of pozzolanic materials are long-term processes, which means, that appropriate durable, and resilient pH electrodes are needed, for direct implantation regarding solid concrete bodies. The purpose of this work was to characterise the potentiometric and surface properties of tungsten electrodes after exposure to extreme alkaline solutions. The tungsten wire surface was activated at 800 °C for 30 min within an oxygen flow. The formation of homogenous and compact multiple layers of WO3 crystals was observed using X-ray diffraction and scanning electron microscopy. X-ray diffraction of thosetungsten electrodes exposed to saturated calcium hydroxide solution or the pore-water of cement-based materials during 10 months, indicated partly dissolved WO3. Two new compounds appeared on the electrodes surfaces; pure tungsten and CaWO4. The presence of tungsten was affecting any potentiometric response in acidic pH region (2-5) but in pH 5-12 region the response still remained linear with a slope of 42 2 mV/pH unit. The W/WO3 electrode was suitable for the long-term monitoring of corrosion processes in concrete-basedmaterials according to the pH changes as it has stable and repeatable responses to alkaline solutions (pH > 12). All the tested interferring ions had no significant influence on electrode potential. The W/WO3 electrode is simple, robust, inexpensive, and temperature resistant and can be applied in potentiometric titrations as well as in batch and flow-injection analysis. The prepared electrode is a highly promising pH sensor for the monitoring of pH changes in highly alkaline capillary water of concrete.
Keywords: pH; potenciometrija; volfram; volframov trioksid